1999
DOI: 10.1177/002215549904700309
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Receptor Long-form Splice-variant Protein Expression in Neuron Cell Bodies of the Brain and Co-localization with Neuropeptide Y mRNA in the Arcuate Nucleus

Abstract: SUMMARYReduced leptin (Ob protein) signaling is proposed to be a stimulus for the activation of neuropeptide Y (NPY) gene activity and increased expression of mRNA for the long form of the leptin receptor (Ob-Rb) in the hypothalamic arcuate nucleus. To determine if Ob-Rb protein is expressed in arcuate nucleus NPY neurons, we developed an affinity-purified polyclonal antibody against amino acids 956-1102 of human Ob-Rb. This antibody specifically recognizes the cytoplasmic tail of Ob-Rb and does not react with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
95
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(104 citation statements)
references
References 56 publications
(66 reference statements)
7
95
0
2
Order By: Relevance
“…2A indicate that the two different leptin receptor antibodies detected the same long and/or short forms of leptin receptors from the hypothalamic and WAT samples on Western blot assays. The sizes of the long and short forms of leptin receptors detected here are consistent with those observed in previous studies (21,(27)(28)(29). The identification of OB-Rb was confirmed by further comparing the immunoreactive bands of the wild-type brain with those of db/db hypothalamic and brain extracts because the db/db mice do not express OB-Rb but maintain the expression of short forms of OBR (4) (Fig.…”
Section: Resultssupporting
confidence: 91%
“…2A indicate that the two different leptin receptor antibodies detected the same long and/or short forms of leptin receptors from the hypothalamic and WAT samples on Western blot assays. The sizes of the long and short forms of leptin receptors detected here are consistent with those observed in previous studies (21,(27)(28)(29). The identification of OB-Rb was confirmed by further comparing the immunoreactive bands of the wild-type brain with those of db/db hypothalamic and brain extracts because the db/db mice do not express OB-Rb but maintain the expression of short forms of OBR (4) (Fig.…”
Section: Resultssupporting
confidence: 91%
“…The amounts of 35 S-labeled leptin receptor paralleled the total number of leptin binding sites (Fig. 3), with HLR-5 having the most labeled protein and HLR-67 the least (data not shown).…”
Section: Resultsmentioning
confidence: 75%
“…This result is supported by other studies on the localization of endogenous receptor in brain. It has been shown that the endogenous long isoform of the leptin receptor is found predominantly within the cell bodies of rat neurons, not at the cell surface (35,36). In addition, immunohistochemical localization studies using an antibody that recognizes all leptin receptor isoforms showed intracellular immunoreactivity in brain, including intense intracellular staining of the choroid plexus epithelium, where it is thought that most of the receptor is the shortest isoform (HLR-5) (36,37).…”
Section: Resultsmentioning
confidence: 99%
“…We recently showed that OB-R internalizes via a clathrin-mediated pathway and is transported to lysosomes where it is degraded. Most OB-Rs (endogenously expressed or transfected) are localized in intracellular membranes (16)(17)(18)(19)(20)(21)28). Importantly, these receptors are fully functional in terms of ligand binding (19,20).…”
Section: Regulation Of Ob-r Trafficking By Ob-rgrpmentioning
confidence: 99%
“…Possible mechanisms underlying this pathological state, termed leptin resistance, are impaired leptin bioavailability and transport across the blood-brain barrier, up-regulation of negative feed-back regulators of OB-R signaling, and defects in OB-R trafficking and signaling (13)(14)(15). Importantly, at steady state, most OB-R (endogenously expressed and transfected) are in intracellular membranes (16)(17)(18)(19)(20)(21) and are fully functional in terms of ligand binding (19,20). However, they are unable to participate in the functional response, as leptin does not penetrate the cell.…”
mentioning
confidence: 99%